Analisis Diksi dan Gaya Bahasa Pidato Presiden Jokowi 2021 Menggunakan Teori Gorys Keraf untuk Bahan Ajar SMP - Medina Fatah, Haulla Putri; Dheni Harmaen; Desti Fatin Fauziyyah (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This study aims to find diction and language style contained in Jokowi's Presidential speech at the 2021 MPR Annual Session by analyzing and utilizing the results of the analysis as an alternative for the preparation of teaching materials for students in grade IX SMP / MTs. This research is descriptive research. Descriptive research is research that describes the results of its analysis in a narrative manner. The data sources in this analysis are the video of President Jokowi's speech at the 2021 MPR Annual Session and several supporting tribes. The results of this analysis contain six types of diction, six types of comparison language style, three types of opposition language style, one type of linking language style, and one type of repetition style. In general, the text of Jokowi's Presidential speech at the 2021 MPR Annual Session uses denotative diction, periphrasis language style, prolepsis or anticipation language style, climax language style, and parallelism language style. The results of this analysis are then adjusted to the demands of the 2013 curriculum which contains Basic Competencies (KD) and Core Competencies (KI). In addition, it is adjusted to the criteria for teaching materials which are assessed based on language aspects, learner psychology, and readability. Then, the results of the analysis are used as alternative teaching materials in the form of modules used by students of grade IX SMP / MTs in learning Indonesian language about Persuasive Speech Texts.